Effects of flow regulation on the movement patterns and habitat use of a potamodromous cyprinid species. Issue 2 (6th May 2015) - Alexandre, C. M.; Almeida, P. R.; Neves, T.; Mateus, C. S.; Costa, J. L.; Quintella, B. R.
Abstract: River regulation for hydroelectricity production results in rapid changes of flow and habitat features, but its effects in the movement patterns of freshwater fish are not well understood. Radiotelemetry was used to track Iberian barbel during a year cycle in non‐regulated and regulated rivers. We applied a kernel density method to estimate and compare home range sizes of the two populations. Seasonal patterns of movement and the intra‐annual variation in habitat preferences were also compared. Barbel inhabiting regulated river exhibit larger and more continuous home and core ranges, in opposition to the smaller and patchy areas used by fish inhabiting the non‐regulated river. Seasonal movements of both populations were differentiated by the drought period. Barbel from the non‐regulated river had to search for suitable refuges, with specific habitat characteristics, in which they remained aggregated during harsh summer conditions. Conversely, barbel from regulated river kept a continuous distribution along the river. This study contributes to the management of regulated rivers by providing insights about which flow components are more altered by hydropeaking operations and which are the most critical annual periods for fish movements. It also suggests several restoration actions, such as the protection of fish summer refuges, the restoration of large‐scale temporal streamflow variability and the reduction of daily rates of discharge rise and fall, which should be continuously monitored in order to increase their efficiency and provide new knowledge. Copyright © 2015 John Wiley & Sons, Ltd.